Shaping Ability of Nickel-Titanium Rotary Instruments in Curved Root Canals - Talati, Ali; Moradi, Saeed; Forgani, Maryam; Monajemzadeh, Ali (Iranian Endodontic Journal, 2013)
Introduction: Disinfection and subsequent obturation of the root canal space require adequate mechanical enlargement of the canals. The purpose of this in vitro study was to compare the shaping ability of Mtwo, RaCe and Medin rotary instruments during the preparation of curved root canals. Materials and Methods: Sixty mesiobuccal root canals of mandibular molars with severe curvatures between 25-35° and radius of 4-9 mm were randomly divided into three groups of 20 canals each. Using pre- and post-instrumentation radiographs, straightening of the canal and the apical transportation were determined with AutoCAD software. The data were analyzed using Chi square, analysis of variance, and post-hoc tests and the significance level was set at P<0.05. Results: Mtwo instruments maintained the canal curvature significantly better than Race and Medin instruments (P<0.05). There was significant difference between the rotary instruments for iatrogenic transportation of the major foramen (P>0.05). Conclusions: Under the conditions of this in vitro study, Mtwo instruments seemed superior to the two other rotary instruments.